ANALYTICAL MODEL OF A DIFFERENTIAL METHOD FOR RECEIVING AND PROCESSING SIGNALS OF THE INFRARED RANGE OF WAVELENGTHS - N. S. Akinshin; Yu. I. Mamon; E. A. Staroguk (Научный вестник МГТУ ГА)
One of the classic methods to improve the noise immunity of passive detection of infrared wavelength range (IKSO) is a differential inclusion of pyrocatechol, placed at some distance. An analytical model of a differential method of receiving infrared radiation from moving objects is introduced. A comparison with experimental results for moving objects of different types is made. Differential inclusion of sensors can be used not only to compensate the external interference, but also to determine the boundaries of a temporary "slot", inside which the movable object is most likely to be detected. The temporal boundaries are used for the decision making about the type and parameters of the movable object in complexional device of object classification.The principle of operation of ikso, which is to record signals with diversity of pyrocatechol into the appropriate memory registers and output detection of the differential signal envelope. Subsequently, from the memory registers portions of a recording signal posted pyrocatechol are selected which are later processed to determine the temporal provisions of minimum minimore and maximum maximore. The direction of movement of the object abeam is determined by the delay or advance of the extrema of the signals of one sensor relative to another within a given temporal "slot".It is shown that aggregation should be the following – the tool with a maximum radius of the zone of sensitivity should be active and the basic, but if there is a more reliable piece of information about the detected object which can implement a more refined classification of the object (for example, a group of people, wheeled vehicles-tracked vehicles, etc.). The conclusion is made about the advantages of differential option to include spaced sensors.The results can be used in the development of infrared wavelengths passive detection in the conceptual design phase.